Mechanical, thermal, and barrier properties of methylcellulose/cellulose nanocrystals nanocomposites - Silvério, Hudson Alves; Flauzino Neto, Wilson Pires; Silva, Ingrid Souza Vieira da; Rosa, Joyce Rover; Pasquini, Daniel; Assunção, Rosana maria Nascimento de; Barud, Hernane da Silva [UNESP]; Ribeiro, Sidney José Lima [UNESP] (FapUNIFESP (SciELO), 2014)
In this work, the effects of incorporating cellulose nanocrystals from soy hulls (WSH30) on the mechanical, thermal, and barrier properties of methylcellulose (MC) nanocomposites were evaluated. MC/WSH30 nanocomposite films with different filler levels (2, 4, 6, 8, and 10%) were prepared by casting. Compared to neat MC film, improvements in the mechanical and barrier properties were observed, while thermal stability was retained. The improved mechanical properties of nanocomposites prepared may be attributed to mechanical percolation of WSH30, formation of a continuous network of WSH30 linked by hydrogen interactions and a close association between filler and matrix.
Keywords: Cellulose nanocrystals; Agro-industrial residue; Reinforcement; Methylcellulose; Nanocomposites